Explaining the successes and failures of tuberculosis treatment programs; a tale of two regions in rural eastern Uganda - Jonathan Izudi; Imelda. K. Tamwesigire; Francis Bajunirwe (BMC, 2019)
Abstract Background Optimally performing tuberculosis (TB) programs are characterized by treatment success rate (TSR) of at least 90%. In rural eastern Uganda, and elsewhere in sub Saharan Africa, TSR varies considerably across district TB programs and the reasons for the differences are unclear. This study explored factors associated with the low and high TSR across four districts in rural eastern Uganda. Methods We interviewed District TB and Leprosy Supervisors, Laboratory focal persons, and health facility TB focal persons from four districts in eastern Uganda as key informants. Interviews were audio recorded, transcribed verbatim, and imported into ATLAs.ti where thematic content analysis was performed and results were summarized into themes. Results The emerging themes were categorized as either facilitators of or barriers to treatment success. The emerging facilitators prevailing in the districts with high rates of treatment success were using data to make decisions and design interventions, continuous quality improvement, capacity building, and prioritization of better management of people with TB. The barriers common in districts with low rates of treatment success included lack of motivated and dedicated TB focal persons, scarce or no funding for implementing TB activities, and a poor implementation of community-based directly observed therapy short course. Conclusion This study shows that several factors are associated with the differing rates of treatment success in rural eastern Uganda. These factors should be the focus for TB control programs in Uganda and similar settings in order to improve rates of treatment success.